2001
DOI: 10.1038/modpathol.3880302
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Loss of Heterozygosity at 1p36.3 and p73 Abnormality in Parathyroid Adenomas

Abstract: Although 1p is one of the most common loci showing loss of heterozygosity (LOH) in primary parathyroid adenoma, fine mapping has not been previously examined. In this study, we analyzed LOH in 32 primary parathyroid adenomas using five microsatellite markers at 1p36 (proximal-D1S507-D1S450-D1S2893-D1S468-D1S243-distal). All cases were heterozygous for at least one marker. The frequency of LOH varied from 41.2% (D1S468) to 7.1% (D1S507) among the different markers. LOH was detected consistently in a group of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…On the other hand, in our present work, LOH of the p73 locus was not observed in all informative (GC/AT heterozygote) CRC cases, although the 1p36 locus is a site observed to have frequent loss of heterozygosity in various human cancers [36]. Pfeifer et al support our finding, since they did not show LOH of the p73 gene in 54 heterozygotic cases [22].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, in our present work, LOH of the p73 locus was not observed in all informative (GC/AT heterozygote) CRC cases, although the 1p36 locus is a site observed to have frequent loss of heterozygosity in various human cancers [36]. Pfeifer et al support our finding, since they did not show LOH of the p73 gene in 54 heterozygotic cases [22].…”
Section: Discussionsupporting
confidence: 80%
“…A region with frequent LOH is 1p36 in different types of cancers, although the frequencies reported vary greatly (17). In addition, the more exact location has not been mapped precisely (17) and therefore we looked at the possibility that the losses could be found around the GC/AT polymorphism of the p73 gene.…”
Section: Discussionmentioning
confidence: 99%
“…One of these genes is p73 (1p36.33), a p53 homologue (10,11). However, extensive mutation studies showed that p73 is rarely mutated in human tumor cells (12)(13)(14). Instead, differential expression of splice variants of p73 seems associated with tumor malignancy.…”
Section: Introductionmentioning
confidence: 99%